Analisis Penerapan Prinsip Etika Bisnis Pada Transaksi Jual Beli Online pada Marketplace Tokopedia Perspektif Yusuf Al-Qardawi - Karina Widya Andari; Yuliani - (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2021)
The increasingly advanced technology requires the entire community to continue to innovate in various activities. One of them is in the economic field. Buying and selling online is an activity that is very much happening in the current era. Not meeting sellers and buyers is one of the gaps in the existence of fraud in business activities. One of the most visited marketplace platforms in Indonesia is Tokopedia. In doing business it is necessary to have ethics, one of the figures who have thoughts about Islamic business ethics is Yusuf al-Qardhawi. The purpose of this study is to analyze the application of business ethics in online buying and selling transactions in the Tokopedia marketplace, Yusuf al-Qardhawi's perspective. The methodology of this research is qualitative with library method (literature research). As a third party that bridges the meeting of sellers and buyers, Tokopedia has applied the principles of Islamic business ethics from the perspective of Yusuf Al-Qardhawi. Tokopedia has a fairly good system to protect business actors in it so that they feel safe and comfortable when making transactions.